THE THEOLOGY OF THE RESURRECTION OF JESUS CHRIST, WITH PARTICULAR REFERENCE TO PAULINE KERYGMA AND SOTERIOLOGY (1978)
The heart of the New Testament message is the resurrection of Jesus Christ; Yet, the nature of the resurrection has remained one of the riddles of Few Testament studies. There is the perennial problem, of the discrepancies between the various accounts of the unique event recorded in the Gospels, Of course, the variances are largely due to differences in theological outlook and varied interests in the early Church. Moreover,' the interest of the evangelists was not in details but in the message. The actual resurrection of Jesus is not within the field of human vision; therefore, to find out what really happened one must start from the post resurrection appearances. But this investigation is chiefly concerned with the resurrection of Jesus as it affects Paul's teaching. The personal encounter with the Risen Lord Jesus on the Damascus road meant for Paul a new beginning. The resurrection of Jesus became central to the whole of Pauline thought on the role of Jesus as Redeemer and man's salvation, both now and in the future. Nevertheless, his 'theology' is not based on the Damascus road experience; it is rooted in the apostolic tradition. It is Paul that gives us the earliest record of the apostolic resurrection tradition. The apostolic kerygma stresses the fact that Jesus was raised bodily from the dead. The death and resurrection of Jesus became the act of God for our present and future salvation. The resurrection of Jesus and the resurrection of the dead are two inseparable facts. Jesus' resurrection forms the basis of Paul's discussion on the resurrection of believers. For Paul the life of a bodiless soul is incomplete, distressingly dull and missing the gift of the Gospel. But the time of the investiture remains unsolved in Paul.